The Moral Values in Niki Caro's Live-Action Movie "Mulan" - Littu, Daniel; Iskandar, Iskandar; Nur, Riola Haya (ELITERATE : Journal of English Linguistics and Literature Studies, 2023)
In this study researcher analysed the moral value in Mulan movie directed by Niki Caro and produced by Walt Disney Pictures. The researcher using the content analysis description technique and referring to the moral theory of James Rachels (2004) to answer the research questions: (1) What kind of moral values are presented in Mulan live-action movie? (2) How are the moral values in “Mulan” movie presented in social-humanity? Base on the findings, there are  four moral values load in the Mulan movie. First, the moral value of courage when she won the battle and saved the emperor. Second, the moral value of generosity when Mulan respects family, village and country. Third, the moral value of honesty when Mulan trying to admit her true identity to Commander Tong. Fourth, the moral value of loyalty in which Mulan fights for the emperor and protects her from those who seek to overthrow the emperor.